Scalability and Reliability Determination of Low-Power Wide Area Network (LPWAN) Architecture - A. Obayuwana; I. A. Edeoghon (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to evaluate the reliability and scalability of Low-Power Wide Area Network (LPWAN) architecture using ns-3 simulation and modelling. The study provides a more comprehensive investigation of the scalability, reliability, and capacity of LoRa networks (LoRaWAN) as the number of end devices grows to hundreds or thousands per gateway. This was achieved by modeling LoRaWAN networks as pure and slotted ALOHA networks, with consideration for important characteristics such as the capture effect. The relationship between transmission rates and spread factor was also investigated. Using the LoRaWAN ns-3 module, a scalability analysis of LoRaWAN shows the detrimental impact on packet delivery ratio (PDR) of increasing the number of nodes per gateway and presents the results of transmission rate at varying spread factors.